Estética e narrativa da Selfie de risco: sobre a imagem sensual do rosto entre a vida e a morte - Abreu, Cíntia Viviane Fernande de (2020)
This research aims to analyze selfies that put the lives of people who tried to take them at risk, more specifically, those made in risky places and situations and / or viralized by a risk narrative; reflecting on self-portrait in contemporary times and its link with danger. Conceiving that the risky selfie, as an image, blurs the threshold between life and death, it is necessary to study photography in depth beyond the traditional notion of representation. For this, we rely on thinkers like Roland Barthes; Walter Benjamin; Georges Didi-Huberman; Giorgio Agamben; Michel Foucault; Gilles Deleuze and Feliz Guatarri; Marie-José Mondzain; Susan Sontag; George Bataille; Emanuel Levinas; Byung-Chul Han and Jacques Aumont. Assuming that the research methodology is qualitative and the analysis is aesthetic, we analyzed five selfies. The results point to a view that selfies and studies on images bring new perspectives on the theories of contemporary images, with new concepts of culture, aesthetics and drives in the world involved by the advancement of technology.